2019
DOI: 10.1016/j.marpolbul.2019.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic accumulation and biomagnification in a coastal marine reserve situated in a sparsely populated area

Abstract: A B S T R A C TToxic chemicals within and adsorbed to microplastics (0.05-5 mm) have the potential to biomagnify in food webs. However, microplastic concentrations in highly productive, coastal habitats are not well understood. Therefore, we quantified the presence of microplastics in a benthic community and surrounding environment of a remote marine reserve on the open coast of California, USA. Concentrations of microplastic particles in seawater were 36.59 plastics/L and in sediments were 0.227 ± 0.135 plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 51 publications
0
26
0
1
Order By: Relevance
“…However, what appears to be more probable is that the seals are ingesting bres indirectly via trophic transfer 21,45 . Previous studies have shown bres to have long body residence times in low-trophic level organisms, which would suggest an increased chance of secondary bre ingestion by predators 43,[46][47][48] . Microplastic bres may be transferred along food chains and re ected in greater proportions among high-trophic level species such as marine mammals 43,46,49 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, what appears to be more probable is that the seals are ingesting bres indirectly via trophic transfer 21,45 . Previous studies have shown bres to have long body residence times in low-trophic level organisms, which would suggest an increased chance of secondary bre ingestion by predators 43,[46][47][48] . Microplastic bres may be transferred along food chains and re ected in greater proportions among high-trophic level species such as marine mammals 43,46,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown bres to have long body residence times in low-trophic level organisms, which would suggest an increased chance of secondary bre ingestion by predators 43,[46][47][48] . Microplastic bres may be transferred along food chains and re ected in greater proportions among high-trophic level species such as marine mammals 43,46,49 . Whether the higher relative number of bres compared to fragments observed here is representative of a biological process such as trophic transfer, or purely an incidental nding, is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations were positively correlated with water depth, and fibers were the most prevalent type of particle identified. Similarly, Saley et al (2019) measured microplastics in a benthic community near a remote marine reserve in California, United States, and found microplastics adhered to macroalgal surfaces at between 2.34 and 8.65 particles per gram. Saley et al (2019) also measured uptake in an herbivorous snail (Tegula funebralis) at higher concentrations than other benthic organisms, 9.91 ± 6.31 particles per gram, implying possible bioconcentration.…”
Section: Invertebratesmentioning
confidence: 99%
“…Moreover, the smaller sizes of microplastic could be a great concern because it could be ingested by planktonic organisms and entrained by settling detritus (Cole et al, 2013;Botterell et al, 2019;Ballent et al, 2013). The entry of smaller size microplastics and nanoplastics in the planktonic food web could lead to further bioaccumulation and biomagnification in higher vertebrates (Saley et al, 2019;Akhbarizadeh et al, 2019). Hence, microplastics size are crucial nominators on determining the impact of microplastics on environment fauna.…”
Section: Introductionmentioning
confidence: 99%